A case of a combination of Crocker - Adamson follicular spinulosa, lichen acuminatus and Little - Lassueur syndrome - N. A. Slesarenko (Vestnik Dermatologii i Venerologii, 2017)
The article describes a clinical case of a combination of Crocker-Adamson follicular spinulosa, lichen acuminatus and Little-Lassueur syndrome in a young man aged 17. The patient had the onset of atopic manifestations at an early age (atopic dermatitis, rhinitis, conjunctivitis) along with disorders related to the process of keratosis. The article provides current data on the etiology, pathogenesis and treatment of these diseases.